The Effectiveness of "Sipentik" as an Authentic Assessment Application for Increasing Student IT Literacy - Hidayah, Falis Ulil; Linuwih, Suharto; Subali, Bambang (Journal of Innovative Science Education, 2023)
MTs and SMP teachers in Rowosari Kendal District have difficulty carrying out authentic assessments manually because the components being assessed and the number of students to be observed are not small, and it takes a lot of time and effort, and they are prone to errors or omissions in the assessment. In addition, they are aware that the assessment is still focused on the cognitive aspects of students through learning achievement tests, while the assessment of attitudes and skills is only at a glance without using assessment instruments, besides that teachers must address technological developments that are increasingly accelerating and it is important to increase students' IT literacy. One of the potential learning methods to help teachers in authentic assessment and improve IT literacy is by applying the Authentic Assessment System (Sipentik) application.. The purpose of this research is to describe and analyze the characteristics of Sipentik as an authentic assessment application for teachers and the effectiveness of the Sipentik application in the teaching and learning process in schools. This type of field research uses a mixed methods approach with an embedded experimental model design , with data collection techniques through documentation, questionnaires, observations, and interviews. The data that has been collected can then be analyzed through quantitative and qualitative data analysis. The results of the study show that: 1) "Sipentik" as an authentic assessment application for teachers has the characteristics of this internet-based application with its main feature being technology for authentically assessing students, besides that it can also help teachers manage the learning system in class more easily and directed, also makes teachers more able to improve IT literacy. 2) The Sipentik application in the teaching and learning process in schools is effective as an authentic teacher assessment to improve students' IT literacy at SMP N 1 Rowosari, 3) The authentic assessment of SMP N 1 Rowosari teachers using the Sipentik application shows better and more effective than using the manual.